Prevalence and Associated Factors of Intestinal Parasitic Infections among Food Handlers in Mettu Town, Southwest Ethiopia - Solomon Yeshanew; Melaku Tadege; Abdulhakim Abamecha (Journal of Tropical Medicine)
Food handlers are important sources of intestinal parasitic infection to the public and mass catering service areas. Several reports worldwide particularly in developing countries showed a high prevalence of intestinal parasitic infections among these groups of individuals. In an attempt to determine the prevalence of intestinal parasites, a cross-sectional study was carried out among food handlers in food establishment areas of Mettu town, Southwest Ethiopia. To collect sociodemographic characteristics of the study participants, a structured questionnaire and physical observation were employed. Stool specimens collected from each food handlers participated in the study were then examined using light microscopy of the wet mount followed by formol-ether concentration methods to see infection status. A total of 139 food handlers were enrolled in the study. Majority of them were females 89 (64%), and 124 (89.2%) of them had not taken any training related to food handling and preparation. Sixty-two (44.6%) of the study participants were diagnosed with one or more intestinal parasites. The chi-square test showed that intestinal parasite infection was found associated with personal hygiene (p ≤ 0.0001), nail trimming status (p ≤ 0.0001), and hair cover status (p ≤ 0.040). The multivariable logistic regression indicated that the risk to be infected with intestinal parasites were related with older age (p ≤ 0.032), food handlers who had no hand wash practices (p ≤ 0.033), who had no food handling and preparation training (p ≤ 0.005), poor personal hygiene (p ≤ 0.0001), who had not taken regular medical checkup (p ≤ 0.008), and whose nail was not trimmed (p ≤ 0.0001). The most abundant intestinal parasite identified was G. lamblia (24, 26.7%) followed by E. histolytica/dispar (22, 24.4%), and A. lumbricoides (15, 16.7%). Twenty-eight (45.2%) study individuals were also found with mixed infections. The study thus revealed a high prevalence of intestinal parasitic infection among apparently healthy food handlers in food establishments of the study area. Mass drug administration for all food handlers working in food establishment areas of the town coupled with health education and training should be initiated urgently.